A note on decomposing differences in poverty incidence using regression estimates: algorithm and example - Sumon Kumar Bhaumik; Ira N. Gang; Myeong-Su Yun (Rutgers University, Department of Economics, 2006)
This paper decomposes differences in poverty incidence (head count ratio) using estimates from a regression equation, synthesizing the approaches proposed in World Bank (2003) and Yun (2004). A significance test is developed for characteristics and coefficients effects when decomposing differences in poverty incidence. The proposed method is implemented for studying differences in poverty incidence between Serbians and Albanians in Kosovo using Living Standard Measurement Survey.
Keywords: C20; I30; 330; Poverty incidence; decomposition; headcount; probit